Partial trisomy (including T-t gene complex) of the chromosome 17 of the mouse. The effect on male fertility and the transmission to progeny - Gregorová, S; Baranov, V S; Forejt, J (Folia biologica, 1981)
The animals with partial trisomy of chromosome 17, Ts(17A1-17B) 43H, were recovered among progeny of females heterozygous for T(16;17)43H "male-sterile" translocation. The trisomics as well as Rb7Bnr/T43H hybrids of both sexes were fertile, although the male fertility was significantly reduced in comparison with T43H/T43H homozygotes and males without chromosomal rearrangements. Ts43H trisomy acts as a semilethal aneuploidy since a significant deficiency of Ts43H animals was observed in progeny of Ts43H parent, while the expected proportion of trisomic embryos was found up to the 18th day of embryonic development.
Keywords: Mice; Heterozygote; geny; fertilita; heterozygot; Animals; trizomie; Genes; mužské pohlaví; Male; Trisomy; Fertility; zvířata; myši